Addition of straw from F1 hybrids of Solanum photeinocarpum accessions from two climatic-ecological zones reduces cadmium uptake by lettuce. Issue 15 (8th December 2021) - Xie, Yongdong; Yu, Xuena; Liang, Le; Zhang, Jianwei; Li, Huanxiu; Tang, Yi; Liao, Ming'An; He, Zhongqun
ABSTRACT: Straw of Solanum photeinocarpum accessions originating from two climatic-ecological zones (Chengdu, in the Mountain-Central Subtropical-Cold Zone; and Ya'an, in the Central Subtropical-Long Spring and Summer-Drought Zone) and their reciprocal F1 hybrids were added to Cd-contaminated soil, and their effects on the growth and Cd accumulation of lettuce were evaluated. Addition of S. photeinocarpum straw significantly increased biomass and decreased Cd content of lettuce, especially the straw of F1 hybrids raised from a Chengdu pollen donor. Shoot biomass was increased by 26.87%and the shoot Cd content was decreased by 25.86% compared with those of the control. The chlorophyll content and net photosynthetic rate were increased in response to the addition of S. photeinocarpum straw, and the effects of straw of reciprocal F1 hybrids were superior to those of the parents. Application of S. photeinocarpum straw promoted osmoticas (soluble sugar, soluble protein, free proline) contents and activities of antioxidant enzymes [superoxide dismutase (SOD), peroxidase (POD), catalase (CAT)], reduced malondialdehyde (MDA) accumulation, and thus effectively improved the resistance of lettuce to Cd stress. S. photeinocarpum straw increased soil pH and organic matter content, and consequently decreased soil exchangeable Cd content, the strongest effect was achieved by application of S. photeinocarpum straw of reciprocal F1 hybrids raised from a Chengdu pollen donor, in response to which the soil exchangeable Cd content was decreased by 29.62% compared with that of the control. Therefore, the application of S. photeinocarpum straw in Cd-contaminated soil promoted growth and reduced the risk of Cd contamination of lettuce plants. The effects of straw from reciprocal F1 hybrids derived from a Chengdu pollen donor were superior to those of straw from the parents, and thus may be effectively used to improve the safe production of lettuce in Cd-contaminated soil.